O impulso da securitização no Brasil depois da regulamentação dos fundos de investimento em direitos creditórios - Gambôa, Celso Augusto (2011)
The securitization of receivables is a form of financial engineering that allows a company with receivables, to raise funds in the financial markets using these receivables as guarantee. This type of financial transaction began in Brazil, with a similar structure to the international financial market, which was subsequently amended with the regulation of Investment Funds in Credit Rights IFCR. This type of investment fund in Brazil was the first that allowed funds with different types of share, senior and subordinate quotations, to work together. It is shown in this study a research with the financial amount of receivables securitization transactions in Brazil before and after the regulations of the Investment Funds in Credit Rights IFCR, which brought forth a large increase in this type of financial transaction on the second period, compared to the first. This study investigated the causes of the increase on the amount of financial transactions with receivables securitization in Brazil after the regulation of Investment Funds in Credit Rights IFCR